Advances in physical organic chemistry. - Williams, Nicholas H.; Harper, Jason B. (Academic Press, 2022)
"Advances in Physical Organic Chemistry, Volume 56 presents the latest reviews of recent work in physical organic chemistry. The book provides a valuable source of information that is ideal not only for physical organic chemists applying their expertise to both novel and traditional problems, but also for non-specialists across diverse areas who identify a physical organic component in their approach to research. Chapters due to be included in this release cover flavin-dependent enzyme catalysed reactions, coacervates and their properties, heavy atom tunnelling, machine learning, acidity and substituent effects. Reviews the application of quantitative and mathematical methods to help readers understand chemical problems Provides the chemical community with authoritative and critical assessments of the many aspects of physical organic chemistry Covers organic, organometallic, bioorganic, enzymes and materials topics Presents the only regularly published resource for reviews in physical organic chemistry Written by authoritative experts who cover a wide range of topics that require a quantitative, molecular-level understanding of phenomena across a diverse range of disciplines"